EDIBLE SPRAY COATING WITH WATER HYACINTH CELLULOSE AND COCONUT HUSK-BASED CARBON BLACK FOR FOOD APPLICATIONS - Azahra, Annisa Nur; Akmal, Raihan Muhammad; Nabila, Pristy Tasya; Bayah, Salsabilla Permata; Fauji, Muhamad Iqbal; Sari, Yessie Widya (Universitas Mataram, 2025)
Food waste and microbial contamination have led to an annual increase in foodborne diseases. One potential solution is the application of an edible spray coating (ESC) as a bioplastic, incorporating antibacterial agents. The spray technique is considered most effective due to its ease of application and controllable thickness. This research evaluates carbon black (CB) derived from coconut husk waste as an antibacterial agent in ESC. Coconut husk was selected because it contains up to 54% lignin. The ESC was formulated using a mixture of hydroxypropyl methylcellulose (HPMC), k-carrageenan, water hyacinth cellulose, and glycerol. Additionally, other antibacterial agents such as silver and chitosan were included as positive controls. The CB was produced through pyrolysis of coconut husk at 700 °C, with nitrogen gas added at a heating rate of 5 °C/min. The water hyacinth cellulose was extracted using a chemical method. In this study, ten ESC formulations were tested with varying concentrations of silver, chitosan, and CB. The resulting ESC viscosities ranged from 16.8 to 46.9 cP. Antimicrobial activity against E. coli and S. aureus demonstrated that ESC with 1.5% w/v CB exhibited antibacterial activity with inhibition zones of (2.2±0.3) mm and (32±3) mm, respectively. The application of ESC on cherry tomatoes and strawberries showed that samples containing CB experienced a lower weight loss over time. This indicates the potential of CB in preventing microbial contamination.